TYPES OF CONCEPTS IN COGNITIVE LINGUISTICS - Fayzulloyeva , Zilola (Scientific practical conference, 2025)
This article examines the typology of concepts within the framework of cognitive linguistics. Concepts are understood as fundamental mental representations that structure human experience and underlie linguistic meaning. The study identifies and describes the major types of concepts—basic, concrete, abstract, embodied, metaphorical, metonymic, and culturally specific—highlighting their cognitive and linguistic characteristics.